Bridging biosafety and biosecurity gaps: DURC and ePPP policy insights from U.S. institutions - Gillum, David R.; Tran, An; Fletcher, Jennifer; Vogel, Kathleen M. (Frontiers in Bioengineering and Biotechnology, 2024)
This study provides empirical data on the knowledge and practices of biosafety and biosecurity professionals and researchers involved in research on enhanced Potential Pandemic Pathogens (ePPPs) and Dual Use Research of Concern (DURC) within various U.S. sectors. The goal is to improve public health interventions and oversight for DURC and ePPP, contributing valuable insights for policy development. A notable finding was the association between larger biosafety/biosecurity teams and a higher likelihood of conducting high-risk biological research. Methods: A survey of 541 biosafety and biosecurity professionals was conducted between March 8 and April 10, 2024, with results analyzed using SAS at a significance level of 0.05. The study received approval from the Institutional Review Boards (IRBs) at Arizona State University and the University of Nevada, Reno. Results: Government organizations were more likely to conduct DURC compared to other sectors (e.g., Academic, Commercial, Consulting). Public institutions reviewed more experiments outside the scope of the U.S. DURC Policy than private for-profit institutions. Institutions with larger biosafety/biosecurity teams reported greater research activity and more effective non-compliance reporting mechanisms (e.g., anonymous hotlines, reporting forms). Additionally, financial support and the challenges of policy implementation varied significantly across sectors. Discussion: The findings emphasize the need for appropriate staffing and resource allocation for high-risk biosafety and biosecurity research. A differentiated regulatory approach and equitable distribution of resources are essential for effective oversight. Moreover, robust noncompliance reporting systems are critical to mitigating the risks associated with DURC and ePPP research. 1 Introduction Research that involves dual use research of concern (DURC) and enhanced potential pandemic pathogens (ePPP) presents unique biosafety and biosecurity hazards when compared to less risky biological research. The terminology used to describe pathogens that have the potential to cause a pandemic has evolved over time from Potential Pandemic Pathogens (PPP) to Enhanced Potential Pandemic Pathogens (ePPP) and most recently to Pathogens with Enhanced Pandemic Potential Research that involves DURC and ePPP presents unique biosafety and biosecurity hazards when compared to less risky biological research (